THE RELATIONSHIP BETWEEN NITRATE, PHOSPHATE AND ORGANIC MATERIAL CONCENTRATION TO PHYTOPLANKTON ABUNDANCE IN RUPAT ISLAND WATERS - Tanjung, Doli Juni Setia; Amin, Bintal; Mubarak, Mubarak (Asian Journal of Aquatic Sciences, 2023)
Over time, Rupat Island has experienced very rapid development, marked by variousactivities such as plantations, agriculture, farming, and ecotourism activities which aregrowing rapidly. This study aims to determine the relationship between concentrations ofnitrate, phosphate, and organic matter on the abundance of phytoplankton in Rupat Islandwaters. The results showed that the average nitrate concentration was relatively high, rangingfrom 0.0993-0.1618 mg/L and the average phosphate concentration was around 0.0951-0.1571 mg/L. Furthermore, the concentration of organic matter in water ranged from 27.555-35.234 mg/L. The lowest abundance of phytoplankton was found in the Station II area with anaverage abundance value of around 416.67 cells/L, while the highest average abundance wasin the Station V area with an average value of 993.05 cells/L. The relationship between thecontent of nitrate, phosphate, and organic matter with the abundance of phytoplankton in theRupat Island area was insignificant or weak with a coefficient of determination (R2) of 8%,10.5% and 3.3%.